Diagnóstico socieconômico: o caso do projeto de assentamento Santa Cruz II- Araguatins (TO) - Oliveira, Raylla Gonçalves de (Universidade Federal do Tocantins, 2023)
The present research aimed to analyze the socioeconomic aspects of the settlers of the agrarian reform of the Santa Cruz II Settlement Project in the municipality of Araguatins-TO, in order to diagnose the difficulties from the perspective of the settlers and the productive reality, specifically with regard to the commercialization of products of animal origin, in the various production chains within family farming, which is the economic base of the territory. Since this analytical construction brings the possibility of working with the productive gaps present in the region, as well as making it possible to know the potential of the main productive practices within the technologies available in the studied region, as well as possibilities for implementing new production chains, considering the vulnerabilities of the animal production systems and the main difficulties faced by the families in the settlement, such as access to commercialization of products. In this study, interviews were carried out with 26 settlers from the Santa Cruz II PA, with different profiles. In the table, people who reported their full name are identified by their initials, which means Unidentified. In the age variable, most people did not provide the information, some because they were uncomfortable to reveal their age and others because they did not ask. In the results obtained, it was observed that most settlers have more people aged 36 years and few people interviewed were younger people. After the results and the interviews carried out in the present work, it was concluded that most of the residents in the settlement PA Santa Cruz II are over 36 years old, have little education and most families receive government benefits.